Reconstructing Legal Responsibility for Digital Signatures: A Socio-Semiotic Perspective in Indonesian Cyber Law - Kadriah, Ayyub; Hasibuan, Faizie Yusuf; Suganda, Atma (Sinergi International Journal of Law, 2025)
Digital signatures play a vital role in facilitating electronic legal transactions. Despite being regulated by various Indonesian laws, their effective implementation remains limited due to gaps in legal culture, institutional readiness, and technical validation. This study addresses two core questions: (1) How is the legal basis for digital signature protection situated within Indonesia’s digital legal culture? and (2) How can a fair legal accountability model be developed? The study offers a novel interdisciplinary perspective by combining legal protection theory, social change theory, legal responsibility theory, and legal semiotics. It frames digital signatures as legal symbols whose meaning has yet to be fully internalized by legal institutions and society. Using a normative-critical and qualitative approach, the study gathers insights from legal practitioners, regulators, academics, and digital signature users through semi-structured interviews. The data are thematically analyzed to identify institutional gaps and social perceptions. Findings indicate that digital signature protection in Indonesia remains overly formalistic. In judicial practice, they are not consistently accepted as legitimate legal evidence. Moreover, there is no strong accountability framework for misuse or digital identity fraud. The study concludes that digital signature protection must go beyond statutory recognition. It requires building legal meaning within society through increased public awareness, technological integration, and institutional reform. The state must develop an inclusive, adaptive framework that unites law, technology, and legal culture to ensure justice and trust in digital legal interactions.